Ayurvedic Management of Recurrent Bartholin’s Cyst - A Case Report - Dr. Madhu M (RGUHS Journal of AYUSH Sciences)
Bartholinrsquos glands are two pea shaped glands located on either sides of labia majora. These secrete mucous which lubricates the vagina. Cysts can occur when secretions are blocked inside the glands due to obstruction in ducts and if untreated can result in abscess. Smaller cysts are asymptomatic and may not require any treatment. However larger cysts cause pain and need medical attention. In Ayurveda these can be correlated to Yoni kanda which is treated with different oral medications and Sthanika chikitsa. Shodhana karma also shows promising results in preventing disease recurrence.